Measured influence of overhead HVAC on exposure to airborne contaminants from simulated speaking in a meeting and a classroom. (3rd September 2021) - Singer, Brett C.; Zhao, Haoran; Preble, Chelsea V.; Delp, William W.; Pantelic, Jovan; Sohn, Michael D.; Kirchstetter, Thomas W.
Abstract: Tracer gas experiments were conducted in a 158 m 3 room with overhead supply diffusers to study dispersion of contaminants from simulated speaking in physically distanced meeting and classroom configurations. The room was contained within a 237 m 3 cell with open plenum return to the HVAC system. Heated manikins at desks and a researcher operating the tracer release apparatus presented 8–9 thermal plumes. Experiments were conducted under conditions of no forced air and neutral, cooled, or heated air supplied at 980–1100 cmh, and with/out 20% outdoor air. CO2 was released at the head of one manikin in each experiment to simulate small (<5 µm diameter) respiratory aerosols. The metric of exposure relative to perfectly mixed (ERM) is introduced to quantify impacts, based on measurements at manikin heads and at three heights in the center and corners of the room. Chilled or neutral supply air provided good mixing with ERMs close to one. Thermal stratification during heating produced higher ERMs at most manikins: 25% were ≥2.5 and the highest were >5× perfectly mixed conditions. Operation of two within‐zone air cleaners together moving ≥400 cmh vertically in the room provided enough mixing to mitigate elevated exposure variations.